2016
DOI: 10.1155/2016/4354136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Mediated Agents on Morphology and Crystallinity of Synthesized Silver Nanowires Prepared by Polyol Process

Abstract: Synthesis and characterization of multiple crystalline silver nanowires (NWs) with uniform diameters were carried out by using 1,2-propandiol and ethylene glycol (EG) as comediated solvents and FeCl3as mediated agent in the presence of poly(vinyl pyrrolidone) (PVP). Experimental data and structural characterizations revealed that AgNWs have evolved from the multiple crystalline seeds initially generated by reduction of AgNO3with EG and 1,2-propandiol followed by reducing Fe(III) to Fe(II) which in turn reacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Consequently, the reaction time following this method is shorter than that of other methods. Finally, in this condition AgNWs with high quality and yield were created by using a mixed solution and FeCl 3 as a mediated agent .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the reaction time following this method is shorter than that of other methods. Finally, in this condition AgNWs with high quality and yield were created by using a mixed solution and FeCl 3 as a mediated agent .…”
Section: Resultsmentioning
confidence: 99%
“…After drying AgNWs a powder form was obtained. For TEM characterization, a suspension of AgNWs was prepared by adding deionized water . All solutions used were made from highly pure chemicals, without any moisture.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis process is chemical reduction of Ag ions in the presence of a polymeric capping agent, in which a small amount of suitable salt can facilitate the growth of the silver seeds to the wire shape [9]. Several factors affect the morphology and yield of AgNWs, including reagent concentration, rate of reagent addition, preparation of the silver ion solution, capping agent molecular weight, type of salt, type and power of stirring, reactor volume in batch synthesis, and residence time in flow synthesis [59][60][61][62][63][64][65][66][67][68][69].…”
Section: Polyol Synthesis and Characterization Of Agnwsmentioning
confidence: 99%
“…Satoungar et al investigated the effect of several mediation agents (FeCl 2 , FeCl 3 , and AlCl 3 ) on the morphology of AgNWs through the use of 1,2-propandiol and EG as a solvent and a reducing agent. They showed that Clions are responsible for electrostatic stabilization and AgCl colloid formation in the initial stage of silver seed formation [68].…”
Section: Effect Of the Salt Mediator In The Polyol Synthesis Ofmentioning
confidence: 99%
“…To acquire purified AgNWs, the mixture was diluted with acetone, deionized water and ethanol, washed and centrifuged 3 times to remove excess of EG and other reaction product. In the whole reaction, the EG acts as both reducing agent and solvent, surfactants such as PVP could control the growth rates of various faces of silver by coordinating to the surfaces, lead silver to grow into uniform nanowires, FeCl3 as mediated and nucleation agent can react with and remove the adsorbed atomic oxygen from silver surfaces [23,24]. Fig.…”
Section: Experimental Materialsmentioning
confidence: 99%